"In all our training, where was this thing called supervision?" Clinical supervision in Kenya. Issue 1 (2nd January 2022) - Kiteki, Bellah N.; Yong, Andrea; Hart, Sotonye Natalie; Onyambu, Faith N.
ABSTRACT: Supervision is in its developmental stages in Kenya. Using a reflective thematic analysis, the authors explored counselors' ( n = 13) experiences and perceptions of supervision. Three key findings from the study were (a) the practice of supervision as less frequent, varied, and limited; (b) up here, and down there: the influence of culture and power in supervision; and (c) the role of the mental health movement in the development of supervision. We provide a background of counseling in Kenya followed by a brief context of supervision and its status in the country. Implications for supervision practice and research are discussed.